Living Hierarchy in Yemen - Meneley, Anne (Anthropologica, 2022)
This article investigates how unequal material relationships permeate the "lived identities" (Williams, 1977) of subordination and domination in the forms of concepts about and enactments of personhood, emotions, piety and propriety among Muslim women of Zabid, Republic of Yemen. I discuss how the gender hierarchy is entwined with wider forms of hierarchy between the elite and a servant class of people, known as the akhdam. Dominant ideas about "appropriately behaved," moral, pious women can serve to make "commonsense" the domination of others who do not constitute themselves in such ways. In short, "moral selves" are created at the same time as "legitimate hierarchies." Styles of female deference to men (control of body and emotion, veiling and avoidance behaviour, which are thought to demonstrate Muslim piety) ensure the subordination of women to men at the same time they legitimize the superiority of elite women over their servants, who do not comport themselves in such ways. Consumption practices are significant as well for the elite as it consumes its wealth in ways that "signify" for reputations: it is channeled into the elements of gracious hospitality or consumed rather than hoarded.